Directly bonded hybrid of graphene nanoplatelets and fullerene: facile solid-state mechanochemical synthesis and application as carbon-based electrocatalyst for oxygen reduction reaction. Issue 8 (10th December 2014) - Guan, Jian; Chen, Xiang; Wei, Tao; Liu, Fupin; Wang, Song; Yang, Qing; Lu, Yalin; Yang, Shangfeng
Abstract : The first directly bonded hybrid of graphene nanoplatelets and C60 is successfully synthesized using a facile solid-state mechanochemical method via ball milling with LiOH as a catalyst. Abstract : Using a facile solid-state mechanochemical method by ball milling, we successfully synthesized the first directly bonded graphene–C60 hybrid, for which LiOH is found to play a crucial role as the catalyst. The hybrid structure of graphene–C60 is confirmed by FTIR, Raman, XRD and XPS characterizations, and its conformation is proposed, featuring the direct bonding of graphene nanoplatelets and C60 via two C–C single bonds. SEM measurement suggests that severe edge distortions occur for graphene–C60 hybrid, and HR-TEM study indicate the covalent attaching of C60 molecules onto the edge of graphene nanoplatelets. The graphene–C60 hybrid is applied as a carbon-based electrocatalyst toward oxygen reduction reaction (ORR), showing improved ORR electrocatalytic activity than the pristine graphite.